2014
DOI: 10.1063/1.4897275
|View full text |Cite
|
Sign up to set email alerts
|

Extended mode in blocked impurity band detectors for terahertz radiation detection

Abstract: We demonstrate the existence of an interfacial barrier in blocked impurity band (BIB) detectors using temperature-dependent dark current and corresponding theoretical calculations. Considering the effects of the interfacial barrier, the calculated photoresponse is in good agreement with the experimental results. A dual-excitation model, including the direct excitation over the full barrier and excitation to the band minimum with subsequent tunneling into the blocking layer, is proposed to quantitatively explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 23 publications
1
13
0
2
Order By: Relevance
“…图片来自文献, 已获得授权 [20] . 图片来自文献, 已获得授权 的方法测量得到, 具体结果如图12所示 [21,22,40] . 图 10 (网络版彩图)样品1-c,1-d和1-e的ECV数据 [20] .…”
Section: 界面对于杂质分布电活性的影响一直未被清晰地认unclassified
See 1 more Smart Citation
“…图片来自文献, 已获得授权 [20] . 图片来自文献, 已获得授权 的方法测量得到, 具体结果如图12所示 [21,22,40] . 图 10 (网络版彩图)样品1-c,1-d和1-e的ECV数据 [20] .…”
Section: 界面对于杂质分布电活性的影响一直未被清晰地认unclassified
“…平面结构的BIB红外探测器如图13(a)所示 [41] . [21,40] . 图片来自文献, 已获得授权 Figure 12 (Color online) (a) SPR data of the epitaxial blocking layer, the active layer, and the buried bottom contact layer, where the buried bottom contact layer was developed using ion implantation; (b) concentration profile of impurity in devices along the growth direction obtained by SIMS where the buried bottom contact layer is thicker than that developed by ion implantation [21,40].…”
Section: 平面结构Si基bib红外探测器材料mentioning
confidence: 99%
“…Since IR and THz detection technology gained further importance in various fields due to the unique advantages of those techniques, blocked-impurity-band (BIB) THz photodetectors were developed in the past decades. [253] BIB devices typically had benefited from a high responsivity, a broadband response, a mature fabrication technique and facile integration with CMOS read-out circuits, while they had been achieved at an expensive cost with a complicated fabrication process. Using a periodic metal structure adopted in the design of the BIB device, Zhu et al demonstrated a superior performance in a new operation mode which suggested the development of lower-cost and potentially mass-producible THz detectors.…”
Section: Optoelectronicsmentioning
confidence: 99%
“…Terahertz (THz) technology has applications in imaging, astronomy, biomedicine and security screening applications for detecting hidden objects [ 28 , 29 , 30 ]. THz radiation typically refers to the electromagnetic radiation in the frequency range from ~0.1 THz to 10 THz, corresponding to wavelengths from 30 μm up to 3 mm [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%